The Influence F Market Conditions and Market Location on Consumer Decisions to Buy Vegetables - Putra Apriliansyah Rohaerdi; Rizka Aliffita Nabilla; Achmad Faqih; Ghazy Faisal Aqimmudin (Pusat Publikasi Nusantara, 2023)
Food needs are basic human needs and are one of the topics that always experience development in accordance with paradigm changes and human lifestyles. The growing awareness of the community with the level of education and higher income, demands that the products available in the market can meet their healthy lifestyle standards according to the understanding they get from the information they get around them. Not only must the product, quality and price but the place must also be clean. This study aims to find out: (1) the influence of market conditions on vegetable purchasing decisions. (2) the influence of market location on the purchasing decisions of vegetable consumers. (3) the influence of market conditions and market location on the purchasing decisions of vegetable consumers. The study was conducted from March to May 2023, using a survey method on 60 consumers who were buying vegetables at the Pasalaran Plered Market, Cirebon Regency using questionnaires as a tool to find out information from respondents. The data used are primary data and secondary data. The data analysis used is descriptive analysis, multiple linear analysis, t test analysis, f test analysis and coefficient of determination. The results of this study are, (1) There is a significant influence of market conditions on consumers who buy vegetables. (2) There is a significant influence of market location on consumers who buy vegetables. (3) Based on market conditions and market location simultaneously affect the purchase of vegetables by consumers